Preparation and Characterisation of LiFePO4/CNT Material for Li-Ion Batteries - Rushanah Mohamed; Shan Ji; Vladimir Linkov (International Journal of Electrochemistry)
Li-ion battery cathode materials were synthesised via a mechanical activation and thermal treatment process and systematically studied. LiFePO4/CNT composite cathode materials were successfully prepared from LiFePO4 material. The synthesis technique involved growth of carbon nanotubes onto the LiFePO4 using a novel spray pyrolysis-modified CVD technique. The technique yielded LiFePO4/CNT composite cathode material displaying good electrochemical activity. The composite cathode exhibited excellent electrochemical performances with 163 mAh/g discharge capacity with 94% cycle efficiency at a 0.1 C discharge rate in the first cycle, with a capacity fade of approximately 10% after 30 cycles. The results indicate that carbon nanotube addition can enable LiFePO4 to display a higher discharge capacity at a fast rate with high efficiency. The research is of potential interest for the application of carbon nanotubes as a new conducting additive in cathode preparation and for the development of high-power Li-ion batteries for hybrid electric vehicles.